PERCEPTIONS OF MARITAL ROLES IN BASIC COMMODITY GROUPS PURCHASE DECISION-MAKING - KANCHEVA, Irina; MARINOV, Giorgi (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
Family plays a primary role in the demand formation in consumer markets worldwide. It is the field where a wide variety of consumer decisions are made every day. Family decisionmaking is a complex process in which multiple individuals combine their personal needs, wants and resources in order to reach a satisfactory outcome. The development of the social system leads to modifications of the known behavioral patterns of the family as a consumption unit. This paper is aimed at present-day Bulgarian family marital role structure. The distribution of roles between spouses was examined across 22 commodity groups using a convenience sample of 215 respondents.